Play-based Learning Activities for Creativity in Children's Dance Movements - Dewi, Melina Surya; Yufiarti (Jurnal Pendidikan Usia Dini, 2021)
Play-based learning activities are important programs throughout the world of children's education. Through play, children learn creatively and constructively. This study aims to solve the problem of creativity in early-childhood dance movements with the hope that there will be an increase in aspects of fluency, flexibility and elaboration through play activities related to educational dance. This action research uses an action research method which is carried out in three cycles. The subjects in this study were 19 children aged 5-6 years in Kindergarten in Central Jakarta. Data collection was carried out through observation, interviews, field notes, video documentation and photos. The findings show every child's creativity in dance movements can be improved through playing activities. Increased creativity in dance movements occurs in the aspects of fluency, flexibility, and elaboration. Another important finding, there is an increase in the optimal ability of dance creativity in the third cycle of this action research. The implication from this research is that play activities suitable for learning creative dance in early childhood must be designed as a program that emphasizes aspects of fluency, flexibility, and elaboration. Keywords: Early Childhood, Creativity in dance movements, Play based learning activities References: Bläsing, B., Calvo-Merino, B., Cross, E. S., Jola, C., Honisch, J., & Stevens, C. J. (2012). Neurocognitive control in dance perception and performance. Acta Psychologica, 139(2), 300–308. https://doi.org/10.1016/j.actpsy.2011.12.005 Brehm, M. A., & McNett, L. (2007). Creative dance for learning: The kinesthetic link. McGraw-Hill. Chatoupis, C. (2013). Young children’s divergent movement ability: A study revisited. Early Child Development and Care, 183(1), 92–108. https://doi.org/10.1080/03004430.2012.655728 Cheng, V. M. Y. (2010). Tensions and dilemmas of teachers in creativity reform in a Chinese context. Thinking Skills and Creativity, 5(3), 120–137. https://doi.org/10.1016/j.tsc.2010.09.005 Cheung, R. H. P. (2012). Teaching for creativity: Examining the beliefs of early childhood teachers and their influence on teaching practices. Australasian Journal of Early Childhood, 37(3), 43–52. https://doi.org/10.1177/183693911203700307 Cleland, F. E., & Gallahue, D. L. (1993). Young Children’s Divergent Movement Ability. Perceptual and Motor Skills, 77(2), 535–544. https://doi.org/10.2466/pms.1993.77.2.535 Copple, C., & Bredekamp, S. (2009). Developmentally Appropriate Practice in Early Childhood Programs Serving Children from Birth through Age 8 (3rd ed.). National Association for the Education of Young Children. Craft, A. (2000). Creativity across the primary curriculum: Framing and developing practice. Routledge. Craft, Anna. (2005). Creativity in Schools: Tensions and Dilemmas. Routledge. Cropley, A. (2001). Creativity in education & learning: A guide for teachers and educators. Kogan Page. Doherty, J., & Bailey, R. (2002). Supporting Physical Development and Physical Education in the Early Years (1st edition). Open University Press. Eckhoff, A. (2011). Creativity in the Early Childhood Classroom: Perspectives of Preservice Teachers. Journal of Early Childhood Teacher Education, 32(3), 240–255. https://doi.org/10.1080/10901027.2011.594486 Garaigordobil, M., & Berrueco, L. (2011). Effects of a Play Program on Creative Thinking of Preschool Children. The Spanish Journal of Psychology, 14(2), 608–618. https://doi.org/10.5209/rev_SJOP.2011.v14.n2.9 Gilbert, A. G. (2019). Brain-compatible dance education (Second Edition). Human Kinetics, Inc. Hoffmann, J. D., & Russ, S. W. (2016). Fostering pretend play skills and creativity in elementary school girls: A group play intervention. Psychology of Aesthetics, Creativity, and the Arts, 10(1), 114–125. https://doi.org/10.1037/aca0000039 Hoffmann, J., & Russ, S. (2012). Pretend play, creativity, and emotion regulation in children. Psychology of Aesthetics, Creativity, and the Arts, 6(2), 175–184. https://doi.org/10.1037/a0026299 Hui, A. N. N., Chow, B. W. Y., Chan, A. Y. T., Chui, B. H. T., & Sam, C. T. (2015). Creativity in Hong Kong classrooms: Transition from a seriously formal pedagogy to informally playful learning. Education 3-13, 43(4), 393–403. https://doi.org/10.1080/03004279.2015.1020652 Jeffrey, B. (2006). Creative teaching and learning: Towards a common discourse and practice. Cambridge Journal of Education, 36(3), 399–414. https://doi.org/10.1080/03057640600866015 Karaca, N. H., Uzun, H., & Metin, Ş. (2020). The relationship between the motor creativity and peer play behaviors of preschool children and the factors affecting this relationship. Thinking Skills and Creativity, 38, 100716. https://doi.org/10.1016/j.tsc.2020.100716 Karpati, F. J., Giacosa, C., Foster, N. E. V., Penhune, V. B., & Hyde, K. L. (2016). Sensorimotor integration is enhanced in dancers and musicians. Experimental Brain Research, 234(3), 893–903. https://doi.org/10.1007/s00221-015-4524-1 Kaufman, J. C., & Beghetto, R. A. (2009). Beyond Big and Little: The Four C Model of Creativity. Review of General Psychology, 13(1), 1–12. https://doi.org/10.1037/a0013688 Kemmis, S., McTaggart, R., & Nixon, R. (2014). The Action Research Planner. Springer Singapore. https://doi.org/10.1007/978-981-4560-67-2 Kuhn, J.-T., & Holling, H. (2009). Exploring the nature of divergent thinking: A multilevel analysis. Thinking Skills and Creativity, 4(2), 116–123. https://doi.org/10.1016/j.tsc.2009.06.004 Lai Keun, L., & Hunt, P. (2006). Creative dance: Singapore children’s creative thinking and problem‐solving responses. Research in Dance Education, 7(1), 35–65. https://doi.org/10.1080/14617890600610661 Leff, S. S., Costigan, T., & Power, T. J. (2004). Using participatory research to develop a playground-based prevention program. Journal of School Psychology, 42(1), 3–21. https://doi.org/10.1016/j.jsp.2003.08.005 Lobo, Y. B., & Winsler, A. (2006). The Effects of a Creative Dance and Movement Program on the Social Competence of Head Start Preschoolers. Social Development, 15(3), 501–519. https://doi.org/10.1111/j.1467-9507.2006.00353.x Lucas, B. (2001). Creative teaching, teaching creativity and creative learning (A. Craft, B. Jeffrey&M. Leibling (Eds),). Continuum. Marinšek, M., & Denac, O. (2020). The Effects of an Integrated Programme on Developing Fundamental Movement Skills and Rhythmic Abilities in Early Childhood. Early Childhood Education Journal, 48(6), 751–758. https://doi.org/10.1007/s10643-020-01042-8 Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (Third edition). SAGE Publications, Inc. Pürgstaller, E. (2021). Assessment of Creativity in Dance in Children: Development and Validation of a Test Instrument. Creativity Research Journal, 33(1), 33–46. https://doi.org/10.1080/10400419.2020.1817694 Repp, B. H., & Su, Y.-H. (2013). Sensorimotor synchronization: A review of recent research (2006–2012). Psychonomic Bulletin & Review, 20(3), 403–452. https://doi.org/10.3758/s13423-012-0371-2 Rudowicz, E., & Hui, A. (2000). Hong Kong Chinese People’s View of Creativity. 16. Runco, M. A. (2003). Education for Creative Potential. Scandinavian Journal of Educational Research, 47(3), 317–324. https://doi.org/10.1080/00313830308598 Runco, M. A., & Acar, S. (2012). Divergent Thinking as an Indicator of Creative Potential. Creativity Research Journal, 24(1), 66–75. https://doi.org/10.1080/10400419.2012.652929 Saracho, O. (2002). Young Children’s Creativity and Pretend Play. Early Child Development and Care, 172(5), 431–438. https://doi.org/10.1080/03004430214553 Schwartz, D., Dodge, K. A., Pettit, G. S., Bates, J. E., & The Conduct Problems Prevention Research Group. (2000). Friendship as a moderating factor in the pathway between early harsh home environment and later victimization in the peer group. Developmental Psychology, 36(5), 646–662. https://doi.org/10.1037/0012-1649.36.5.646 Steinberg, C., & Steinberg, F. (2016). Importance of students’ views and the role of self-esteem in lessons of creative dance in physical education. Research in Dance Education, 17(3), 189–203. https://doi.org/10.1080/14647893.2016.1208646 Stinson, S. W. (1993). Testing Creativity of Dance Students in the Peoples Republic of China. Dance Research Journal, 25(1), 65–68. https://doi.org/10.1017/S0149767700008056 Tsompanaki, E. (2019). The Effect of Creative Movement-Dance on the Development of Basic Motor Skills of Pre-School Children. Review of European Studies, 11(2), 29. https://doi.org/10.5539/res.v11n2p29